Exploring the impact of online education on student engagement in higher education in post-COVID-19: what students want to get? - Deng, Ziqi; Yang, Zhi (Frontiers in Psychology, 2025)
The sudden outbreak of COVID-19 has led to an unprecedented impact on traditional higher education classrooms. To ensure that students can continue receiving quality education, online learning has become a mainstream mode of instruction. Therefore, increasing student engagement become a key priority for teachers in online teaching contexts. Few reviews examine student engagement in education in the post-COVID-19 era. To address this gap, the present study aims to explore the key factors that influence student engagement in classroom settings in this context. We identified 30 papers related to our research focus from 498 articles retrieved from the Web of Science and Scopus databases, following the 2020 PRISMA framework. After reviewing related studies, this study examined the characteristics of student engagement about cognitive, affective, and behavioral dimensions. We also analyzed the impact of online education on student engagement. Our findings suggest that emotional, cognitive, and behavioral engagement are interconnected and influence one another. In addition, teachers’ support for students’ cognitive and emotional needs plays a vital role in fostering their behavioral engagement. This article can help educators better understand the definition of engagement and the factors that influence student engagement in the classroom.